O Padroado da coroa de Portugal: fundamentos e práticas - Xavier, Ângela Barreto (2018)
Early Modern definition of rights of Patronage. The specific characteristics of the Portuguese Patronage and the erosion of the full patronage of the Order of Christ, approaching the Castilian model of the patronage on Spanish America. Evolution of the ecclesiastical geography of the Portuguese patronage on extra European territories (16th-18th centuries). Reasons for the persistence of the patronage of the Order of Christ.